2020
DOI: 10.1042/etls20200153
|View full text |Cite
|
Sign up to set email alerts
|

Nano-vehicles give new lease of life to existing antimicrobials

Abstract: Antibiotic resistance has become one of the greatest challenges for modern medicine, and new approaches for the treatment of bacterial infections are urgently needed to avoid widespread vulnerability again to infections that have so far been easily treatable with existing drugs. Among the many approaches investigated to overcome this challenge is the use of engineered nanostructures for the precise and targeted delivery of existing antimicrobial agents in a fashion that will potentiate their effect. This idea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The composition was created so that the penicillin would remain bound to the dendrimers and could effectively deactivate the close surrounding of bacteria [ 236 ]. Choi et al tested dendrimers-based vancomycin conjugates, and these nanostructures bound were tested against vancomycin-resistant and non-resistant S. aureus with nano-molar affinity [ 237 ]. A recent study carried out by G. Jiang et al showed that heterofunctionalization poly-(amido-amine) (PAMAM) dendrimers that were conjugated with vancomycin and further incorporated with AgNPs showed a significant reduction in bacterial colonies of S.aureusstrains [ 238 ].…”
Section: Silver Nanoparticles and Antibacterial Activitymentioning
confidence: 99%
“…The composition was created so that the penicillin would remain bound to the dendrimers and could effectively deactivate the close surrounding of bacteria [ 236 ]. Choi et al tested dendrimers-based vancomycin conjugates, and these nanostructures bound were tested against vancomycin-resistant and non-resistant S. aureus with nano-molar affinity [ 237 ]. A recent study carried out by G. Jiang et al showed that heterofunctionalization poly-(amido-amine) (PAMAM) dendrimers that were conjugated with vancomycin and further incorporated with AgNPs showed a significant reduction in bacterial colonies of S.aureusstrains [ 238 ].…”
Section: Silver Nanoparticles and Antibacterial Activitymentioning
confidence: 99%
“…Targeted delivery of anticancer drugs to target cells in cancer therapy research has inspired more precise and targeted delivery of existing antimicrobial agents through the use of engineered nanostructured materials which can bypass the barriers that prevent traditional pharmacological approaches [ 115 , 116 ]. Some recent studies involving biofilm elimination have shown that nanoparticles can kill bacteria directly or release biocides that disrupt biofilm formation, thereby reducing microbial survival [ 117 , 118 ].…”
Section: Prevention and Treatment Of Iaimentioning
confidence: 99%
“…Drug delivery vehicles have been widely employed to encapsulate and deliver conventional antibiotics, improving their therapeutic index while minimizing their adverse effects [ 5 , 6 , 7 ]. These have shown unprecedented advantages such as enhancement of the effectiveness of existent antibiotics, by enhancing the physicochemical properties and stability of antibiotics and prolongation of antibiotic release, in addition to the capability of targeted delivery to the site of infection as an effective antimicrobial therapy [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%